Application of hard and soft acid base theory to uncover the destructiveness of Lewis bases to UiO-66 type metal organic frameworks in aqueous solutions. Issue 26 (22nd June 2021) - Wang, Liangjie; Li, Juan; Cheng, Luyao; Song, Yonghui; Zeng, Ping; Wen, Xianghua
Abstract : Metal organic frameworks (MOFs), emerging adsorbents and catalysts in the wastewater treatment field, are subject to destruction by Lewis bases in wastewater, such as F − and PO4 3− . Abstract : Metal organic frameworks (MOFs), emerging adsorbents and catalysts in the wastewater treatment field, are subject to destruction by Lewis bases in wastewater, such as F − and PO4 3− . To promote the application of MOFs in wastewater treatment, it is imperative to clarify the mechanism of the destructiveness of L-bases to MOFs. Accordingly, in this study, we performed a series of deliberately designed experiments and theoretical analyses. The ligand release of MOFs in solutions of various L-bases indicated that the order of destructiveness of L-bases to UiO-66-type MOFs was OH − > F − > PO4 3− > AsO4 3− > SO4 2− > CO3 2− = Ac − = Cl − = Br − = NO3 − = 0. To elaborate the intrinsic nature of the destructiveness of L-bases to MOFs based on hard and soft acid base theory, density functional theory was used to calculate the various physicochemical parameters of L-bases related to their strength, including chemical potential ( μ ), Mulliken electronegativity ( χ = − μ ), chemical hardness ( η ), local softness for electrophilic attack ( s − ) and charges of coordinating atoms (CCA). Among these parameters, μ (− χ ) and CCA can reflect the destructiveness of L-bases to MOFs to a large extent, with higher μ (− χ ) and CCA indicating higher destructiveness. To more accurately judge the destructiveness of L-bases to MOFs, integrated use of both μ (− χ ) and CCA is suggested. Additionally, the stability of some UiO-66-type MOFs cannot be well judged by μ (− χ ) and CCA due to the deformation of their ligand structure caused by the steric hindrance of the functional groups of the ligand.